Analisis Keefektifan Kalimat dalam Artikel "Sejarah Dunia" Edisi Oktober 2024 di sejarahkita.com sebagai Media Pembelajaran Sejarah Progresif - Zunaida Nur’aini; Naya Deansita Maheswari; Shofa Saida Khusna; Elsa Dwi Auliya; Imam Nur Rohim; Asep Purwo Yudi Utomo; Riri Kumalasari; Iwan Hardi Saputro (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2025)
This research is motivated by the fact that effective sentences in historical articles can be a path to progressive learning. The article “Sejarah Dunia” (World History), October 2024 edition on sejarahkita.com, was chosen as the object of research because of its relevance as a medium that can provide historical information in a clear and interesting way. Therefore, this study aims to analyze the effectiveness of sentences in articles that are directed at history education, which not only focus on facts but also on the development of critical thinking skills. The method used is descriptive qualitative with listening and recording techniques. The author analyzes the sentence structure, word choice, coherence between sentences, and the chronological flow of the article using distributional and matching methods. The collected data will be tabulated to identify syntactic errors, accuracy of diction, and spelling. The findings show that the article contains a number of shortcomings in sentence structure, where the message conveyed is less clear. However, in some ways, the article also succeeds in conveying an informative and relevant history. This study will provide benefits and insights into effective sentences in historical articles to provide a basis for readers to understand various suggestions and models for progressive learning oriented towards critical thinking. In addition, this study also provides added value by preserving historical values through an easy and interesting presentation.